Negative selection by an endogenous retrovirus promotes a higher-avidity CD4+ T cell response to retroviral infection. - George R Young; Mickaël J-Y Ploquin; Urszula Eksmond; Munisch Wadwa; Jonathan P Stoye; George Kassiotis (PLoS Pathogens)
Effective T cell responses can decisively influence the outcome of retroviral infection. However, what constitutes protective T cell responses or determines the ability of the host to mount such responses is incompletely understood. Here we studied the requirements for development and induction of CD4+ T cells that were essential for immunity to Friend virus (FV) infection of mice, according to their TCR avidity for an FV-derived epitope. We showed that a self peptide, encoded by an endogenous retrovirus, negatively selected a significant fraction of polyclonal FV-specific CD4+ T cells and diminished the response to FV infection. Surprisingly, however, CD4+ T cell-mediated antiviral activity was fully preserved. Detailed repertoire analysis revealed that clones with low avidity for FV-derived peptides were more cross-reactive with self peptides and were consequently preferentially deleted. Negative selection of low-avidity FV-reactive CD4+ T cells was responsible for the dominance of high-avidity clones in the response to FV infection, suggesting that protection against the primary infecting virus was mediated exclusively by high-avidity CD4+ T cells. Thus, although negative selection reduced the size and cross-reactivity of the available FV-reactive naïve CD4+ T cell repertoire, it increased the overall avidity of the repertoire that responded to infection. These findings demonstrate that self proteins expressed by replication-defective endogenous retroviruses can heavily influence the formation of the TCR repertoire reactive with exogenous retroviruses and determine the avidity of the response to retroviral infection. Given the overabundance of endogenous retroviruses in the human genome, these findings also suggest that endogenous retroviral proteins, presented by products of highly polymorphic HLA alleles, may shape the human TCR repertoire that reacts with exogenous retroviruses or other infecting pathogens, leading to interindividual heterogeneity.